2011
DOI: 10.2215/cjn.02540311
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Triiodothyronine Levels with Carotid Atherosclerosis and Arterial Stiffness in Hemodialysis Patients

Abstract: SummaryBackground and objectives End-stage renal disease is linked to alterations in thyroid hormone levels and/or metabolism, resulting in a high prevalence of subclinical hypothyroidism and low triiodothyronine (T3) levels. These alterations are involved in endothelial damage, cardiac abnormalities, and inflammation, but the exact mechanisms are unclear. In this study, we investigated the relationship between serum free-T3 (fT3) and carotid artery atherosclerosis, arterial stiffness, and vascular calcificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 38 publications
5
52
0
1
Order By: Relevance
“…At a cardiac level, low T3 levels in CKD patients are associated with reduced left ventricular function, increased left ventricular mass (13), and elevated intimamedia thickness (12). Our study also adds novel evidence regarding the association between trimestral T3 variation and all-cause and CV mortality in ESRD.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…At a cardiac level, low T3 levels in CKD patients are associated with reduced left ventricular function, increased left ventricular mass (13), and elevated intimamedia thickness (12). Our study also adds novel evidence regarding the association between trimestral T3 variation and all-cause and CV mortality in ESRD.…”
Section: Discussionsupporting
confidence: 54%
“…However, growing evidence suggests participation of T3 in the pathophysiology of endothelial dysfunction (11), atherosclerosis (12), and cardiac abnormalities (13) of CKD patients. Some studies, with somewhat conflicting results, have also implicated thyroid alterations in the mortality risk of CKD patients (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction has been reported in patients with hypothyroidism. Yilmaz et al (114) reported a strong correlation between decreased fT3 and endothelial dysfunction in stage 3 to 4 CKD patients and Tatar et al (115)(116) reported an association of low fT3 and several parameters of CVD mortality, such as endothelial dysfunction and inflammation in HD and PD patients. Dyslipidemia is common in CKD and it can be aggravated by the altered thyroid metabolism observed in these patients (18).…”
Section: Dousdampanis Et Almentioning
confidence: 99%
“…Recent advances in our understanding of the thyroid system have strongly implicated both subclinical hypothyroidism and low free triiodothyronine (fT3) levels in the cardiac and atherosclerotic abnormalities observed in non-renal patients 10) . On the other hand, Tatar et al recently demonstrated that low fT3 levels are associated with carotid atherosclerosis in HD patients 11,12) . Yilmaz et al demonstrated a relationship between low fT3 levels and endothelial dysfunction in patients suffering from renal failure 13) .…”
Section: Biochemical Measurementsmentioning
confidence: 99%